The Relation of Fiber Intake, Cholesterol, and Physical Activity with Blood Cholesterol Level of Women Adult in Bogor Aerobic Studio - Maharani, Adinda; Marjan, Avliya Quratul; Puspareni, Luh Desi (Universitas Islam Negeri Walisongo Semarang, 2018)
This study aims to analyze the relation between fiber intake, cholesterol, nutritional status, and physical activity with blood cholesterol level on adult women. The study design was a cross sectional study. The study involved 60 adult women (aged 40-64 y.o) in the Sanggar Senam Bugar Sehat Bogor as respondent. The analysis used was Chi-square test to assess the relation between variables. The result showed a signinificant relation of physical activity (p value=0,027, OR=0,098 ; 95% CI=0,012-0,809), fiber intake (p value=0,046, OR=7,724 ; 95% CI=0,918-64,260), and cholesterol intake (p value=0,000, OR=16,00 ; 95% CI=3,398-75,345) with blood cholesterol level. It is concluded that blood cholesterol levels are influenced by eating pattern, physical activities, and routine medical check up.